STRATEGI PEMASARAN BERAS PADA AGROINDUSTRI DI KABUPATEN BOJONEGORO: STRATEGI PEMASARAN BERAS PADA AGROINDUSTRI DI KABUPATEN BOJONEGORO - Darsan, Darsan; Yusuf Dawud , Moh (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2021)
The research objective is to want to know what strategies are used for marketing rice in the agro-industry in Bojonegoro district. The hypothesis of this research is that it is assumed that rice marketing must have a marketing strategy for planning, pricing, and distributing. This research method using purposive sampling method. The research population taken as respondents is the agro-industry which sells rice throughout the year. In accordance with the criteria, the population is less than 100 people, so the sample is taken at 10% - 15%. Based on these opinions, the samples of this study were 5 rice agro-industries. The analysis used in this research is the SWOT analysis, which is a qualitative analysis carried out by examining internal and external factors. The conclusion from the calculation results of the SWOT analysis. Internal factors that affect the rice agro-industry business are utilizing the quality of the product with a good taste image and strategic location and adding packaging variants to develop rice marketing. External factors affecting agro-industry business are replacing manual technology with efficient technology to improve the quality of rice production. A good alternative strategy that can be done for the development of rice marketing in the rice agro-industry is the strength of opportunity strategy (Aggressive), which takes advantage of existing strengths to take advantage of opportunities. Keywords: Rice Agrindustry, Bojonegoro Regency, SWOT Analysis.